2017
DOI: 10.1021/acsomega.7b00054
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Oxygen Reduction Reaction Activity and Durability of Platinum–Nickel Nanowires through Synthesis and Post-Treatment Optimization

Abstract: For the first time, extended nanostructured catalysts are demonstrated with both high specific activity (>6000 μA cm Pt –2 at 0.9 V) and high surface areas (>90 m 2 g Pt –1 ). Platinum–nickel (Pt—Ni) nanowires, synthesized by galvanic displacement, have previously produced surface areas in excess of 90 m 2 g Pt –1 , a significant breakthrough in and of itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(123 citation statements)
references
References 56 publications
5
116
2
Order By: Relevance
“…In previous RDE measurements we have observed losses in ECA and specific activity associated with Ni loss from ex-situ acid leaching prior to testing, which is due to a dealloying effect. 37 This is consistent with measurements of PtNi NSTF, which have also showed that Ni loss from the core of the material resulted in decreased activity. 9 We have found that PtNiNWs lose less Ni during RDE testing than the MEAs presented here, which may explain some of this large difference.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In previous RDE measurements we have observed losses in ECA and specific activity associated with Ni loss from ex-situ acid leaching prior to testing, which is due to a dealloying effect. 37 This is consistent with measurements of PtNi NSTF, which have also showed that Ni loss from the core of the material resulted in decreased activity. 9 We have found that PtNiNWs lose less Ni during RDE testing than the MEAs presented here, which may explain some of this large difference.…”
Section: Resultssupporting
confidence: 90%
“…37,38 The PtNiNW materials used as the basis for this work have demonstrated exceptionally high mass activity and electrochemical surface area (ECA) in rotating disc electrode (RDE) studies of inherent catalytic properties. 37,39 We commonly refer to these catalyst structures as nanowires, although on many occasions the transition metal core has been removed and they could alternatively be referred to as nanotubes. The nanowires we have investigated generally are up to 10's of microns in length (as-synthesized) with diameters typically between 100-300 nm.…”
mentioning
confidence: 99%
“…To further improve its stability under normal PEFC operation, future work will focus on tuning the aerogel nanochain structure and surface vs. bulk composition, as to minimize Ni dissolution from the alloy catalyst. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Nanocatalysts with superior ORR activity, such as nanostructured and mesostructured thin films, Pt and PtNi nanowires, PtM aerogels and hollow PtM NPs,, have recently been synthesized. A record ORR specific activity of 11.5 mA cm −2 Pt at 0.90 V vs .…”
Section: Oxygen Reduction Reaction Electrocatalysis In Acidic Electromentioning
confidence: 99%